Palliative Care in Portugal—From Intention to Reality, What Is Yet to Be Accomplished - Marques, Paulo (2023)
Objectives: This article focuses on exploring the evolution of palliative care in Portugal. Ten years after the approval of its Basic Law, the aim was to investigate the quality of the path followed and the guidelines that could promote its development. Thus, this study sought to identify (a) the goals of the current members of parliament concerning palliative care, (b) the major priorities that should guide the development of palliative care in the coming decade, (c) the facilitating or hindering factors to accelerating the process, and (d) to propose consensually agreed measures for the integral development of palliative care within the health system. Methods: The qualitative data analysis was performed through the reading of the literature and interviews conducted via Zoom with several intentionally chosen participants. The data extracted from the previous studies were analyzed in a focus group. The NVivo® 10 was used for the data processing and categorization. Results: Three key themes emerged concerning the current status of palliative care: the policymakers, the health professionals, and the society. This first line of structuring is explained by a second set of categories, namely, (a) the knowledge about palliative care; and (b) palliative care organization from the policymakers’ perspective. In the health professionals’ domain: (a) knowledge about palliative care, (b) clinical training, and (c) medical specialty. Finally, in society: (a) knowledge about palliative care. Significance of the results: Advancing general education, increasing the qualitative training for different health professionals, reformulating the laws supporting them, promoting the flexibility of the implementation methodologies, and establishing a medical specialty are crucial to achieving the proposed goal. This study was not registered.